Population Abundance of Scales (Hemiptera: Diaspididae) and The Parasitoids on the Apple Crop - Khojin Supriadi (Journal of Tropical Life Science, 2019)
These last few years, scales pest infestation on the apple crop in Batu city is a problem that has yet to be controlled. Scales infestations are always there at the apple crop but different population levels at each stage of the apple crop growth. Patterns of population abundance of scales that are synchronized with the apple crop growth stages need to be understood and the basis for the control of scales infestation. The study was conducted in July 2012 until January 2013 in Bumiaji, Batu City. The study was conducted at two locations that have a different altitude, each in Binangun village the altitude of Â± 900 meters above sea level and in the Tulungrejo village that have altitude Â± 1.515 meters above sea level. Results from this study are the pattern of population abundance of scales are linear with the average level of high population caused not found parasitoid as a result of excessive use of insecticides and biodiversity is low. The pattern of population abundance of scales began to rise sharply in the phase of thinning and covering of apple fruit. If required the application of insecticide should be addressed at the time of first instar scales and adult males, but it must be carried out carefully so as not to kill non-target insects.